Treponema pallidum specific IgM haemagglutination test for serodiagnosis of syphilis. Issue 6 (December 1984) - Sato, T; Kubo, E; Yokota, M; Kayashima, T; Tomizawa, T
Abstract : The Treponema pallidum specific IgM haemagglutination (TP-IgM-HA) test uses erythrocytes sensitised with antiserum to human IgM to separate IgM from IgG in serum. Specific antitreponemal IgM captured in this way is detected by adding a second reagent comprising erythrocytes sensitised with T pallidum antigen. Eighty two serum samples from 82 patients with untreated syphilis, 521 samples from 73 patients with treated syphilis, and 1872 samples from people who did not have syphilis were examined by the 19S(IgM)-TPHA (T pallidum haemagglutination), IgM-FTA-ABS (fluorescent treponemal antibody absorbed), TP-IgM-ELISA (enzyme linked immunosorbent assay), and TP-IgM-HA tests for the presence of 19S(IgM) antibodies specific to treponemes. The sensitivity of the TP-IgM-HA test was 97.6% and the specificity was 99.7%. We also traced IgM specific to treponemes in untreated patients with primary syphilis by four different tests. The TP-IgM-HA test results clearly reflected the effect of the treatment.